Swan in the Grail - Holloway, Sue (GaiaQuest, 1999)
Keywords: Ethics; Swans; Ecofeminism; dept.wgs; faculty_collection

Seventh annual Women’s studies conference on Latina issues - Neverow, Vara (Gender, Technology and Development, 1997)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-018-885-049-565 tex.type: [object Object]
Keywords: dept.wms

A potential wolf in sheep's clothing: the ambiguity of "Cooperation.". - Holloway, Sue (Journal of Education, 1992)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-931-288-974-864 tex.type: [object Object]
Keywords: dept.wms

Eves journey: feminine images in hebraic literary tradition. - Holloway, Sue (Anthropology of Consciousness, 1991)
Nehama Aschkenasy Eves Journey: Feminine Images in Hebraic Literary Tradition Philadelphia: University of Pennsylvania Press, 1986. ISBN 0‐8122‐8033‐4. Hardcover, $36.95. Pp. xv+269. Copyright © 1991, Wiley Blackwell. All rights reserved
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00208 tex.type: [object Object]
Keywords: dept.wms